Development and Validation of the Ethicotherapy Quality of Life Questionnaire - Pokladnikova, Jitka; Haviger, Jiri (Journal of religion and health, 2021)
At present, no standardized tool to measure therapeutic outcomes of a central European traditional healing system called Ethicotherapy exists. Ethicotherapy focuses on the relationship between physical health and moral health. The aim was to develop and validate the Ethicotherapy quality of life questionnaire (EQLQ) using a sequential exploratory mixed-method study design. An EQLQ with good psychometric properties was developed. An exploratory factor analysis identified eight domains consisting of 30 items. Future research investigating a relationship between EQLQ, health, and physical illness in different populations and cultural settings is recommended.
Keywords: Factor Analysis, Statistical; Validation; faktorová analýza statistická; Quality of Life; průzkumy a dotazníky; kvalita života; Research Design; reprodukovatelnost výsledků; Development; Humans; Psychometric properties; lidé; výzkumný projekt; psychometrie; Surveys and Questionnaires; Reproducibility of Results; Psychometrics; Questionnaire; Ethicotherapy